Twins in African and diaspora cultures : double trouble, twice blessed. - Peek, Philip M. (Indiana University Press, 2011)
In Africa, where the birthrate of twins is among the highest in the world, twins can be seen as a burden to their families and a threat to the social order, or they can be seen as a gift from God and beings with unique abilities who bring about social harmony. Philip M. Peek and the contributors to this illuminating, multidisciplinary volume explore this rich cultural heritage by examining topics such as twins in artistic representation, twins and divination, and twins in performance, cosmology, religion, and popular culture -- Présentation de l'éditeur.